Renovations of objectives and tasks for science-technology development in Vietnam - Long, Hoang Xuan; Phuong, Nguyen Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Through various long periods, the objectives and tasks of science-technology (S&T) development pass changes in the ways they get defined. The changes are seen clearly in many aspects: service for socio-economic development, development of science-technology in general and development of every S&T sector in particular. The changes were seen also in selection of orientations and focuses of development, and time mark points of achievement. Also it is seen that the relations between objectives and tasks of S&T development are mutually correlated and one is the precondition for another, The changes in the past are highly worth to note. At the same time, the practice puts down requirements of efforts for further changes of objectives and tasks of S&T development in our country. Here it is necessary to pay attentions to objectives and tasks which reflect the S&T development as well as its time mark points, to the shift from the objectives defined in the model of consecutive development to the ones defined in the model of break-through moves and to the unity between objectives and solutions of realization. These renovations are meaningful in making contributions to S&T development in substantial and deeply argumented basis.